Clinicopathological study of soft tissue sarcoma-retrospective study of tertiary cancer institute in eastern India - K. P., Kunhi Mohammed; Pradhan, Snehasis; Bhattacharyya, Supratim; Das, Prafulla Kumar; N. K., Muhammed Navas (International Journal of Research in Medical Sciences, 2020)
Background: Soft tissue sarcomas are a rare and heterogeneous group of malignant tumors of mesenchymal origin that comprise less than 1 percent of all adult malignancies. Although they occur anywhere in the body, they involve most commonly in extremities, trunk, retroperitoneum and head and neck. The aim of the study was to analyze clinical and histopathological features of various soft tissue sarcomas. Methods: This was a retrospective study, conducted in tertiary cancer centre in Odisha during the period 2015 to 2018. We collected clinical parameters like age, sex, site of swelling, any associated pain and biopsy reports and these variables were correlated with final histopathology reports. Results: A total of 107 patients were included in the study, with male to female ratio of 2:1(71 and 36) and average age of 43.45 years. All of them presented with a swelling. The lower extremities were the most common sites i.e. 44.62%. Pleomorphic sarcoma was the most frequent histologic variety comprising 43% and less frequent variety were angiosarcoma, and myxoid sarcoma. Conclusions: Soft tissue sarcoma are predominant in males and middle aged population are frequently affected. Most common affected site is lower extremity and pleomorphic sarcoma is the prominent histologic type.